Development of a Pictorial Semi-Structured Child Anxiety and Coping Interview (CACI): Preliminary Analysis with School Children aged 5–7 years. (22nd October 2018) - Ruocco, Sylvia; Freeman, Nerelie C.; McLean, Louise A.
Abstract : This school-based study reports on the development and preliminary analysis of the new pictorial semi-structured Child Anxiety and Coping Interview (CACI). Participants included 195 children ( M age = 6.71; SD age = .76) drawn from 29 primary schools located in Western Sydney, Australia. The study used a mixed qualitative and quantitative design. The CACI was used to elicit the children's self-report on their problems, emotions, coping strategies, and coping self-efficacy. Qualitative content and thematic analysis were used to code the children's nominated coping strategies for their problems in the home and school contexts. The top five most common problems reported were as follows: fear of spiders or insects, fear of the dark, going places without parents, doing badly at school, and heights. The top five most common coping strategies reported by the children were support seeking, behavioural avoidance, solving the problem, facing the challenge, and behavioural distraction. Self-reported negative emotional intensity was highest for fear of the dark. Coping self-efficacy for fear of the dark was also high, suggesting the children found their coping strategies helpful, including those that were maladaptive. The clinical implications of these findings are discussed.